Pemetaan Faktor Tutupan Lahan (C) Berbasis Transformasi NDVI pada Wilayah Potensi Karst Kawasan Pembangunan JJLS di Kabupaten Gunungkidul - Dila Nur Naningsih; Peter Eka Rosadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The construction of the Jalur Jalan Lintas Selatan (JJLS) in Girijati Village, Purwosari District, Gunungkidul Regency, aims to improve regional connectivity but also has the potential to trigger land degradation and soil erosion. This study aims to map vegetation density and determine the land cover coefficient (C factor) as a basis for erosion mitigation. The method applied is remote sensing analysis using Landsat 8 satellite imagery from January 2026, processed with the Normalized Difference Vegetation Index (NDVI) algorithm. The results indicate that areas surrounding the JJLS development are predominantly characterized by moderate to sparse vegetation, particularly in the central and southern parts (DTH 1A and DTH 1B). In contrast, the northern area (DTH 2) is dominated by dense vegetation, which is relatively more resistant to erosion. These findings suggest the need for conservation strategies such as revegetation, terracing, and proper drainage maintenance in areas surrounding the road infrastructure to minimize surface erosion rates.